2019
DOI: 10.1111/cpr.12629
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue–derived stromal cells’ conditioned medium modulates endothelial‐mesenchymal transition induced by IL‐1β/TGF‐β2 but does not restore endothelial function

Abstract: Objectives Endothelial cells undergo TGF‐β–driven endothelial‐mesenchymal transition (EndMT), representing up to 25% of cardiac myofibroblasts in ischaemic hearts. Previous research showed that conditioned medium of adipose tissue–derived stromal cells (ASC‐CMed) blocks the activation of fibroblasts into fibrotic myofibroblasts. We tested the hypothesis that ASC‐CMed abrogates EndMT and prevents the formation of adverse myofibroblasts. Materials and methods Human umbilical vein endothelial cells (HUVEC) were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 70 publications
(150 reference statements)
2
8
0
Order By: Relevance
“…1C). This change in morphology is consistent with other studies’ observations of EndMT in HUVECs (Yu et al 2017; Liguori et al 2019; Noseda et al 2004). Furthermore, we observed enhanced migratory properties of the HUVECs after SOX9 expression, as shown by transwell assays (Fig.…”
Section: Resultssupporting
confidence: 93%
“…1C). This change in morphology is consistent with other studies’ observations of EndMT in HUVECs (Yu et al 2017; Liguori et al 2019; Noseda et al 2004). Furthermore, we observed enhanced migratory properties of the HUVECs after SOX9 expression, as shown by transwell assays (Fig.…”
Section: Resultssupporting
confidence: 93%
“…In our study, 1 month after MI, the mRNA expression of TGFβ2 was still upregulated compared with WT control, implying TGFβ2's important role in cardiac remodeling in the long term (Figure 2e). It has been demonstrated that IL-1β and TGFβ2 acted synergistically to induced EndMT in human umbilical vein endothelial cells (Liguori, Liguori, Moreira, & Harmsen, 2019;Maleszewska et al, 2013) and this effect is also confirmed in HCAECs in our study. Taken together, these results indicated that the inflammatory microenvironment after MI potentiated EndMT.…”
Section: Discussionsupporting
confidence: 86%
“…HAECs are commonly recognized as a substitute for the basic research study of endothelial cells. Fourth, numerous researches had proved that HG-induced EndMT contributed to endothelial damage ( Maleszewska et al, 2013 ; Liguori et al, 2019 ; Guan et al, 2020 ), which lead to cardiovascular diseases in diabetes. Thus, our study focus on the role of CaSR in HG-induced EndMT, which might underlie the mechanism cardiovascular diseases in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of serum glucose is believed to be the key to promoting the association between endothelial damage and cardiovascular disease ( Giugliano et al, 2019 ; Joffre et al, 2020 ; Liberale et al, 2020 ). Previous studies have shown that high glucose (HG) induces endothelial cell (EC) damage via endothelial-to-mesenchymal transition (EndMT) ( Maleszewska et al, 2013 ; Liguori et al, 2019 ), which contributes to endothelial injury and subsequent cardiovascular disease in DM. However, the underlying mechanisms of HG-induced EndMT remain largely unclear.…”
Section: Introductionmentioning
confidence: 99%